Application of five-element music therapy combined with acupoint applicaiton in postoperative rehabilitation nursing of an elderly patient undergoing resection of colonic polyps (五行音乐疗法联合穴位贴敷缓解1例老年患者结肠息肉电切术后不良反应的康复护理体会) - ZHANG Hongyan (张红燕) (中西医结合护理)
This paper summarized the application of five-element music therapy combined with acupoint applicaiton in relieving the postoperative adverse reactions in an elderly patient undergoing resection of colonic polyps. A comprehensive nursing assessment was conducted based on the concept of Traditional Chinese Medicine sydromn differentiation. Nursing interventions including targeted health education and psychological support, monitoring of vital signs during operation, diet management, pain control and rehabilitation exercise after opertation were carried out. In addition, five-element music therapy combined with acupoint application were conducted to relieve postopetative adverse reactions such as anxiety, sleeping disorder and pain, and improve the recovery of gastrointestinal function and qulity of life of the patient. (本文总结五行音乐疗法联合穴位贴敷缓解1例老年患者结肠息肉电切术后不良反应的康复护理体会。基于全面的护理评估和中医辨证施护原则, 术前开展针对性的健康宣教与心理支持, 术中严密监测生命体征, 术后实施精细化的饮食管理、疼痛护理及康复活动指导。在此基础上, 结合五行音乐疗法与穴位贴敷的非药物干预措施, 形成综合护理方案, 有效改善患者的焦虑情绪、睡眠质量, 减轻疼痛, 促进胃肠功能恢复, 提升术后康复质量。)